Health-Care Providers' Perspectives on Decision-Making Among Seriously Ill Patients of South Asian Origin in the United States - Khosla, Nidhi; Washington, Karla T; Mukherjea, Arnab; Aslakson, Rebecca (Journal of palliative care, 2019)
Persons of South Asian origin (SAs) are the fastest growing minority group in the United States. Culturally competent care for patients and families of SA origin necessitates an understanding of the cultural factors that affect decision-making for palliative and end-of-life care. To better understand health-care providers' perspectives on decision-making among seriously ill persons of SA origin. Data were collected in a US Midwestern city, predominantly in 2 hospital-based health-care systems along with a few interviews of private practitioners. Researchers conducted a thematic analysis of data. Transcripts were coded individually, coding disagreements resolved through discussion and themes arrived upon by consensus. Health-care providers reported that numerous factors interact to influence decision-making among SAs. Patient-based factors include education, time spent in the United States, expectations of physician-directed care, and spiritual beliefs. Family-based factors include a norm of family-based decision-making and a complex distribution of decision-making responsibilities among family members. Provider-based factors include challenges reconciling SA and American approaches to decision-making. Community-based factors include negative attitudes and a lack of education regarding palliative care and the potential role of community support in health-care decision-making. A rich cultural context influences health-care decision-making among seriously ill SAs. An understanding of this context will enhance providers' cultural competence and likely improve services to this growing population.